Hydration, methylene blue, and thiamine as a prevention regimen for ifosfamide-induced encephalopathy - Gharaibeh, Eyad Z; Telfah, Mohammad; Powers, Benjamin C; Salacz, Michael E (Journal of oncology pharmacy practice, 2019)
Ifosfamide is an alkylating chemotherapeutic agent used in the treatment of many malignancies. Ifosfamide-induced encephalopathy is one potential side effect that represents a major drawback to ifosfamide therapy and often necessitates discontinuation of chemotherapy. Previous reports demonstrate moderate effectiveness of prophylactic methylene blue at thwarting ifosfamide-induced encephalopathy. This is a report of a 64-year-old female with relapsed double-hit diffuse large B-cell lymphoma who developed severe altered mental status and neurological symptoms after receiving a second dose of ifosfamide as part of her salvage standard dose R-IE (rituximab, ifosfamide, etoposide), in preparation for chimeric antigen receptor T-cell therapy. Ifosfamide was stopped and extensive metabolic and infectious workups, in addition to brain images, were all unremarkable. Her symptoms were attributed to ifosfamide. Prior to initiating cycle 2 of R-IE, she was started on prophylactic oral thiamine 100 mg, once a day, one week prior to her admission, methylene blue 50 mg intravenous every 6 h (for a total of four doses) and intravenous hydration with normal saline starting on day one of admission. Ifosfamide was administered in the standard dose 2000 mg/m , days 1-3 as continuous intravenous infusion over 24 h. She tolerated the first two days of ifosfamide well and only developed mild encephalopathy during her last dose of ifosfamide. Her symptoms resolved completely without any intervention the following day and she completed all scheduled doses. She eventually received chimeric antigen receptor T-cell therapy. Our report demonstrates the use of hydration, methylene blue, and thiamine as a successful secondary prevention regimen for ifosfamide-induced encephalopathy.